HUBUNGAN PENGETAHUAN GIZI, POLA MAKAN DAN TINGKAT KEPATUHAN DIET DENGAN TEKANAN DARAH PASIEN HIPERTENSI RAWAT JALAN DI RUMAH SAKIT MOHAMMAD HOESIN PALEMBANG - Susyani, Susyani; Hartati, Yuli; Afriani, Lesy (Publikasi Penelitian Terapan dan Kebijakan, 2014)
Hypertension is a blood pressure exceeding 140 mmHg The systolic blood pressure and 90 mmHg for diastolic. Some people call it The Silent Killer . WHO estimates that hypertension causes one out of every eight deaths , which makes hypertension causes the third major killer in the world Report of the Health Research in 2010 , the prevalence of hypertension in Indonesia reached 31.7 % in the population aged 18 and over. This fact indicates hypertension to be one cause of illness in Indonesia. The purpose of this study was to determine the relationship of the level of knowledge of nutrition, diet and dietary compliance with blood pressure in hypertensive patients in outpatient Mohammad Hoesin Hospital Palembang. This type of study is a survey of a cross sectional analytic approach . The population in this study were hypertensive outpatient in hospital Mohammad Hoesin Palembang . The data were analyzed using the chi-square test . The samples size in this study was 49. The results show ( 57.1 % ) of respondents male sex . A total of 89.8 % of the respondents including age groups at risk, as much as 67.3 % of respondents to normal nutritional status , 83.7 % of respondents did not smoke , 61.2 % of respondents did not have a history of hypertension, 44.9 % of respondents have a moderate knowledge level , 53.1 % often consume foods high in sodium , 57.1 % were not adherent to the diet. A total of 81.6 % had high systolic blood pressure and diastolic blood pressure 77.6 % higher. The statistical test results obtained there is a correlation between high- sodium diet ( p = 0.008 ) , and dietary adherence ( p = 0.003 ) and systolic blood pressure.There is a correlation of high sodium diet ( p = 0.02 ) , and dietary adherence ( p = 0.005 ) and diastolic blood pressure .There is no correlation between with systolic and diastolic blood pressure .